1997
DOI: 10.1021/bi970051h
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Sequence Environment Modulates the Disruption by Osteogenesis Imperfecta Glycine Substitutions in Collagen-like Peptides

Abstract: Ostoegenesis imperfecta (OI) or "brittle bone" disease is associated with mutations in the genes for type I collagen chains and produces variable phenotypes, ranging from lethal cases at birth to mild cases with increased bone fractures. The most common OI mutations are single base substitutions leading to replacement of Gly by another residue, breaking the typical (Gly-X-Y)n repeating sequence pattern of the collagen triple-helix. Triple-helical peptides were designed to focus on residues 892-921 of the alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 39 publications
7
69
0
1
Order By: Relevance
“…The implication that Gly f Ser mutations with low T m [+1] values result in lower-than-expected stability is supported by experimental peptide results reported here (Table 6) and elsewhere (33). Lower stability, folding rate, and calorimetric enthalpy were observed for peptide GPOSPAGFA, with low T m [+1] and high T m [-1] values, than for peptide GFASPAGPO, with the positions of the high-and low-stability triplets reversed.…”
Section: Discussionsupporting
confidence: 85%
“…The implication that Gly f Ser mutations with low T m [+1] values result in lower-than-expected stability is supported by experimental peptide results reported here (Table 6) and elsewhere (33). Lower stability, folding rate, and calorimetric enthalpy were observed for peptide GPOSPAGFA, with low T m [+1] and high T m [-1] values, than for peptide GFASPAGPO, with the positions of the high-and low-stability triplets reversed.…”
Section: Discussionsupporting
confidence: 85%
“…In particular it has been observed that large and charged residues generally lead to more severe OI types. [7][8][9] Here we have shown that the local mechanical properties of single tropocollagen molecules can be predicted based on the physical properties of the replacing residue.…”
Section: Resultsmentioning
confidence: 96%
“…Some trends are apparent, such as OI severity increasing with an amino to carboxyl terminal orientation and with substitution by large and charged amino acids. [7][8][9] At present, however, genotype-phenotype correlations are too weak to accurately predict the phenotypic effect of a particular glycine mutation. Indeed, the answer to the question how a single point mutation in the tropocollagen molecule can cause the failure of the entire skeletal system still remains a mystery.…”
Section: Introductionmentioning
confidence: 99%
“…Local sequences N-terminal to the mutation site could also influence the propensity for renucleation, if the Gly substitution has interrupted the C-to N-terminal propagation of the triple helix (40,41). Calculations of relative stabilities, assigned on the basis of the frequency of different tripeptides in collagen, suggest that mutations within a very stable local environment result in a more severe clinical effect (36,42), and studies on peptides have supported the influence of local triplets surrounding a mutation on its disruptive effect (43,44). Cooperative blocks that undergo local breathing or microunfolding could also be destabilized selectively by Gly substitutions and prevent folding of the molecule (2,12).…”
Section: Discussionmentioning
confidence: 99%